2005
DOI: 10.1037/0882-7974.20.2.317
|View full text |Cite
|
Sign up to set email alerts
|

Adult Age Differences in the Implicit and Explicit Components of Top-Down Attentional Guidance During Visual Search.

Abstract: Two experiments investigated adult age differences in the explicit (knowledge-based) and implicit (repetition priming) components of top-down attentional guidance during discrimination of a target singleton. Experiment 1 demonstrated an additional contribution of explicit top-down attention, relative to the implicit effect of repetition priming, which was similar in magnitude for younger and older adults. Experiment 2 examined repetition priming of target activation and distractor inhibition independently. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
42
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 45 publications
(124 reference statements)
8
42
0
Order By: Relevance
“…In a recent study, we examined adult age differences in top-down attention during colour singleton discrimination in a letter search task (Madden, Whiting, Spaniol, & Bucur, 2005). Consistent with Wolfe et al (2003), we found that top-down attention has both explicit (expectation) and implicit (repetition priming) components.…”
mentioning
confidence: 69%
See 4 more Smart Citations
“…In a recent study, we examined adult age differences in top-down attention during colour singleton discrimination in a letter search task (Madden, Whiting, Spaniol, & Bucur, 2005). Consistent with Wolfe et al (2003), we found that top-down attention has both explicit (expectation) and implicit (repetition priming) components.…”
mentioning
confidence: 69%
“…In addition, although the rate of priming for both targets and distractors was similar for younger and older adults, and both age groups exhibited some additional contribution of the explicit component, this latter contribution was greater for older adults than for younger adults. The Madden et al (2005) results suggest that older adults may enhance the output of feature module(s), through explicit top-down attention.…”
mentioning
confidence: 88%
See 3 more Smart Citations